Microvesicles and diabetic complications — novel mediators, potential biomarkers and therapeutic targets - Wang Ying; Chen Li-ming; Liu Ming-lin (Acta Pharmacologica Sinica, 2016)
Ying WANG1, Li-ming CHEN1, *, Ming-lin LIU2, * 1Key Laboratory of Hormones and Development (Ministry of Health) Metabolic Diseases Hospital and Tianjin Institute of Endocrinology, Tianjin Medical University, Tianjin 300070, China; 2Section of Endocrinology, Diabetes and Metabolic Diseases, Department of Medicine, Temple University School of Medicine, Philadelphia, PA 19140, USA Microvesicles (MVs), also known as microparticles, are small membrane vesicles released from different cell types under different conditions. MVs have been detected in the circulation and in organs/tissues in various diseases, including diabetes. Patients with different types of diabetes and complications have different cellular MV patterns. Studies have shown that MVs may mediate vascular thrombosis, vascular inflammation, angiogenesis, and other pathological processes of the disease through their procoagulant, pro-inflammatory, pro-angiogenic, proteolytic, and other properties. Therefore, MVs contribute to the development of diabetic macrovascular and microvascular complications. In addition, clinical studies have indicated that changes in MV number and composition may reflect the pathophysiological conditions of disease, and therefore, may serve as potential biomarkers for diagnostic and prognostic use. Understanding MVs’ involvement in the pathophysiological conditions may provide insight into disease mechanisms and would also be helpful for the development of novel therapeutic strategies in the future. Here, we review the latest publications from our group and other groups and focus on the involvement of MVs in diabetic complications. Keywords: microvesicles; microparticles; diabetes; thrombosis; vascular inflammation; endothelial dysfunction; angiogenesis; diabetic nephropathy; diabetic retinopathy; cardiovascular disease Li-ming CHEN is supported by National Natural Science Foundation of China (NSFC) 81273915 and 81072922. Ming-lin LIU is supported by American Heart Association (AHA)-Great Rivers Affiliate Beginning Grant-In-Aid and Temple University Department of Medicine Career Development Award. * To whom correspondence should be addressed. E-mail xfx22081@vip.163.com (Li-ming CHEN); mlliu02@gmail.com (Ming-lin LIU) Received 2013-09-10 Accepted 2013-12-12